Flood preparedness in rural flood-prone area: a holistic assessment approach in Bangladesh - Md Mostafizur Rahman; Ifta Alam Shobuj; Md. Rabiul Islam; Md. Rakibul Islam; Md. Tanvir Hossain; Edris Alam; Khawla Saeed Al Hattawi; Md Kamrul Islam (Geomatics, Natural Hazards & Risk)
Despite the many fatalities and injuries, Bangladesh lacks holistic individual flood preparedness studies. This study evaluates flood preparedness in the flood-prone rural region of Dowarabazar Upazila, Sunamganj District, Bangladesh. The field survey had 596 respondents. As required, we implemented Spearman’s rank correlation and multiple linear regression. Flooding affected the study population, which made people feel extremely unsafe. Most respondents warned that floods might affect their homes. Many participants reported receiving flood-related information from locals. Most participants reported not being notified of flood forecasts and warnings in their area. The majority indicated that they sought refuge in flood shelters. A significant portion of the participants in the study were unaware of flood preparedness. Loss minimization and adaptability are deficiencies. Concerning flood preparedness, gender, age, occupation, monthly income, multiple sources of income, and house type are all significant determinants. According to field research, females are less prepared for flooding than males. Individuals with pucca housing are better equipped than those with unsafe housing (kacha). Authorities should thus take these factors into account while enhancing flood preparedness. In addition to implementing measures such as improving livelihood patterns and conducting educational campaigns, it is imperative to construct holistic flood preparedness.